2017
DOI: 10.1007/s00520-017-3585-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemotherapy-induced nausea: the role of neurokinin-1 (NK1) receptor antagonists

Abstract: Chemotherapy-induced nausea (CIN) has a significant negative impact on the quality of life of cancer patients. The use of 5-hydroxytryptamine-3 (5-HT3) receptor antagonists (RAs) has reduced the risk of vomiting, but (except for palonosetron) their effect on nausea, especially delayed nausea, is limited. This article reviews the role of NK1RAs when combined with 5-HT3RA–dexamethasone in CIN prophylaxis. Aprepitant has not shown consistent superiority over a two-drug (ondansetron–dexamethasone) combination in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
1
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 68 publications
3
38
1
6
Order By: Relevance
“…The roles of different NK 1 RAs in the prevention of nausea were recently analyzed. 27 Studies of APR have not shown consistent superiority over a 2-drug combination (ondansetron-DEX) in the control of nausea after cisplatin or AC HEC. 27 In addition, no clear conclusions can be inferred on the clinical significance of combining rolapitant and granisetron-DEX with regard to nausea outcomes (HEC or MEC setting).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The roles of different NK 1 RAs in the prevention of nausea were recently analyzed. 27 Studies of APR have not shown consistent superiority over a 2-drug combination (ondansetron-DEX) in the control of nausea after cisplatin or AC HEC. 27 In addition, no clear conclusions can be inferred on the clinical significance of combining rolapitant and granisetron-DEX with regard to nausea outcomes (HEC or MEC setting).…”
Section: Discussionmentioning
confidence: 99%
“…27 Studies of APR have not shown consistent superiority over a 2-drug combination (ondansetron-DEX) in the control of nausea after cisplatin or AC HEC. 27 In addition, no clear conclusions can be inferred on the clinical significance of combining rolapitant and granisetron-DEX with regard to nausea outcomes (HEC or MEC setting). 27 The addition of NETU to PALO (as the fixed-combination antiemetic NEPA) suggested results superior to those obtained with PALO alone in controlling nausea, with overall NSN rates, for 4 cycles, ranging from 75% to 80% after NEPA administration, versus 69% to 76% after PALO.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the addition of NK-1RAs to the combination of 5-HT 3 RA and dexamethasone has significantly reduced rates of emesis in CINV, control of nausea, especially in the delayed phase, remains a clinical challenge. [13][14][15][16]23 Given the subjective nature of measuring nausea, 17 patients may find it easier to report the presence or absence of nausea (using NN) rather than the varying degrees of nausea (using NSN), rendering NN a more quantifiable endpoint than NSN. 14,16 In this analysis, rolapitant significantly improved NN rates during the delayed and overall phases in patients receiving carboplatin-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 The NK-1RAs aprepitant and netupitant have reported inconsistent results. 13 The primary endpoint of many clinical trials evaluating CINV is complete response (CR), defined as no emesis and no use of rescue medication (RM; ie, antiemetics used after chemotherapy administration). 14,15 This endpoint may not reflect the experience of patients receiving chemotherapy, 16 as patients may experience nausea without emesis or vice versa.…”
Section: Introductionmentioning
confidence: 99%